First record of cestode cysts of Phyllobothrium delphini (Phyllobothriidae) from dusky dolphins (Lagenorhynchus obscurus) off Argentine coast - Loizaga de Castro, Rocío; G. Vales, Damián; Degrat, Mariana; García, Néstor; Fernández, Mercedes; A. Crespo, Enrique (HIDROBIOLÓGICA, 2017)
The dusky dolphin, Lagenorhynchus obscurus, is a coastal small cetacean widespread in the southern hemisphere. Here, we present the first record of cestode parasites present in the blubber of dusky dolphin off Argentine coast. The host examined, corresponded to a 15 years old mature female and measured 171 cm long. Cysts of helminths belonging to Cestoda were found on the subcutaneous blubber of the ventral surface; parasites were determined as Phyllobothrium delphini (Phyllobothriidae). Probably the presence of this parasite is related to deep pelagic foraging habitats where the most important prey are the squids. In the stomach contents 25 Type II larvae of Anisakis were found and 12 cephalopod beaks, belonging to argentine shortfin squid, Illex argentinus. Nematodes were found in the intestines, Type II larvae of Anisakis, and another from the genus Stenurus (family, Pseudaliidae). Here a new record of cestodes cysts is described, enriching the parasite-host record for dusky dolphins, enlarging the scarce parasitological information for cetaceans of Argentina.